Defining the impact of melanopsin missense polymorphisms using in vivo functional rescue - Rodgers, J; Hughes, S; Pothecary, C; Brown, L; Hickey, D; Peirson, S; Hankins, M (Oxford University Press, 2018)
Melanopsin (OPN4) is an opsin photopigment expressed within intrinsically photosensitive retinal ganglion cells (ipRGCs) that mediate non-image forming (NIF) responses to light. Two single nucleotide polymorphisms (SNPs) in human melanopsin (hOPN4), Pro10Leu and Thr394Ile, have recently been associated with abnormal NIF responses to light, including Seasonal Affective Disorder. It has been suggested these behavioural changes are due to altered melanopsin signalling. However, there is currently no direct evidence to support this. Here we have used ipRGC-specific delivery of hOPN4 wildtype (WT), Pro10Leu or Thr394Ile adeno-associated viruses (AAV) to determine the functional consequences of hOPN4 SNPs on melanopsin-driven light responses and associated behaviours. Immunohistochemistry confirmed hOPN4 AAVs exclusively transduced mouse ipRGCs. Behavioural phenotyping performed before and after AAV injection demonstrated that both hOPN4 Pro10Leu and Thr394Ile could functionally rescue pupillary light responses and circadian photoentrainment in Opn4-/-mice, with no differences in NIF behaviours detected for animals expressing either SNP compared to hOPN4 WT. Multi-electrode array recordings revealed that ipRGCs expressing hOPN4 Thr394Ile exhibit melanopsin-driven light responses with significantly attenuated response amplitude, decreased sensitivity and faster offset kinetics compared to hOPN4 WT. IpRGCs expressing hOpn4 Pro10Leu also showed reduced response amplitude. Collectively these data suggest Thr394Ile and Pro10Leu may be functionally significant SNPs, which result in altered melanopsin signalling. To our knowledge, this study provides the first direct evidence for the effects of hOPN4 polymorphisms on melanopsin-driven light responses and NIF behaviours in vivo, providing further insight into the role of these SNPs in melanopsin function and human physiology.